Keseimbangan Kehidupan-Kerja, Komitmen Organisasi, dan Perilaku Kewargaan Organisasi Karyawan Bank Syariah - Ghaisa Marin Hartono; Arum Etikariena (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2021)
PT Bank Syariah XYZ is currently working to improve company efficiency by bringing out the organizational citizenship behavior of its employees. Organizational citizenship behavior is an initiative behavior of employees, beyond their required job duties. Based on social exchange theory, organizational citizenship behavior can be generated if there is an equal two-way exchange between employees and the organization. Previous studies also shown that by giving employees an opportunity to get a work-life balance, employee commitment to the organization will increase and leads to the emergence of organizational citizenship behavior among them. Therefore, this study aims to examine the effect of work-life balance on employee organizational citizenship behavior through the role of organizational commitment as a mediator. This research is a quantitative study using an adaptive questionnaire: OCB-C short version from Spector et al. (2010), the work-life balance scale from Hill et al. (2001), and Organizational Commitment from Mowday (1979). Respondents were 154 permanent employees of PT Bank Syariah XYZ Head Office. The analysis results by PROCESS Hayes showed the coefficient value = .42; p < .05; R2 = 28%; 95% CI [.25, .60]. This means that organizational commitment acts as a complete mediator on the effect of work-life balance on organizational citizenship behavior with a proportion of 28% of the total effect of the model. The results of this study are expected to provide insight for the organization to creat more positive work behavior by implementing proactive policies that can minimize conflicts between work and personal life